Посткомуністичні режими = A Concise Field Guide to Post-Communist Regimes Актори, інституції та динаміка - Magyar, Bálint (Academic Studies Press, 2023)
The unanticipated and unsolicited Russian aggression against Ukraine in February 2022 highlighted the urgency of updating general assumptions about post-communist countries. The war has revealed the inadequacy of the terms and concepts employed for western democracies for describing, understanding, and predicting the developments in the "hybrid" regimes of Eastern Europe and the former USSR. Magyar and Madlovics strongly argue for a vocabulary and grammar tailored to the specifics of the countries of the former communist bloc. In this concise companion to the 800-page The Anatomy of Post-Communist Regimes (CEU Press, 2020), they develop a conceptual framework in 120 propositions with (1) a typology of post-communist regimes and (2) a detailed presentation of ideal-type actors and the political, economic, and social phenomena in these regimes. Each of the 120 propositions contains a statement and a succinct discussion supported by illustrative tables, figures, and QR-codes that connect the interested reader to the more detailed analysis in the Anatomy. In a condensed form, the holistic approach of the Anatomy is retained by treating political, market, and communal spheres as parts of a single, coherent whole. An analysis of twelve countries illustrates the concrete application of the method.